Challenges of Education in Indonesia in Facing Fossil Energy Problems and Renewable Energy Use - Faiz Mudhofir; Edy Cahyono; Sigit Saptono; Sulhadi Sulhadi (International Journal of Social Learning (IJSL), 2025)
Global demand for fossil energy continues to increase, affecting both the environment and energy availability. This study aims to describe the energy crisis and its impacts, the adoption of renewable energy (RE), and the educational challenges in addressing these problems in Indonesia.  The Systematic Literature Review method was conducted using Harzing’s Publish or Perish application, which indexed articles from Scopus and Google Scholar, using the keywords “energy crisis,” “renewable energy,” “energy education Indonesia,” and “impact of fossil energy.” The review covered publications from 2017 to March 2025. A total of 116 articles met the eligibility criteria. The results indicate that the environmental impacts include increases in CO2 emissions driven by urbanization, industrialization, and transportation. Globally, RE adoption remains at only 1%. The use of renewable energy in Indonesia is relatively low, at 11.31% of the available energy supply. Indonesia’s educational strategies include establishing specialized schools for the development of RE, curriculum support, and implementing project-based learning. These strategies must be replicated and further developed by other institutions. Through these efforts, Indonesia is expected to become more aware of the limitations and impacts of fossil energy and better able to utilize the availability of renewable energy.